2018
DOI: 10.1007/s11605-018-3726-9
|View full text |Cite
|
Sign up to set email alerts
|

The Additional Value of Laparoscopic Ultrasound to Staging Laparoscopy in Patients with Suspected Pancreatic Head Cancer

Abstract: Background This study aimed to evaluate the additional value of laparoscopic ultrasound (LUS) to staging laparoscopy (SL) for detecting occult liver metastases in patients with potentially resectable pancreatic head cancer. Methods A retrospective cohort study was performed including all patients who underwent SL and LUS between 2005 and 2016. LUS was performed during SL to detect liver metastases not found by preoperative imaging or visual inspection of the liver. Results Out of 197 patients, visual inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, its relevance remains under debate. [18] Nevertheless, we wanted to highlight that 12% of patients in our series who underwent an exploratory laparoscopy were nally found to have a contraindication to resection intraoperatively (with a "short" delay from laparoscopy to exploration of 18 days). This suggested that negative exploratory laparoscopy did not systematically imply a resection, mainly because it is di cult to explore major vasculature involvement in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, its relevance remains under debate. [18] Nevertheless, we wanted to highlight that 12% of patients in our series who underwent an exploratory laparoscopy were nally found to have a contraindication to resection intraoperatively (with a "short" delay from laparoscopy to exploration of 18 days). This suggested that negative exploratory laparoscopy did not systematically imply a resection, mainly because it is di cult to explore major vasculature involvement in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, its relevance remains under debate. [19] Nevertheless, we wanted to highlight that 12% of patients in our series who underwent an exploratory laparoscopy were nally found to have a contraindication to resection intraoperatively (with a "short" delay from laparoscopy to exploration of 18 days). This suggested that negative exploratory laparoscopy did not systematically imply a resection, mainly because it is di cult to explore major vasculature involvement in this way.…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopy is not routinely performed worldwide and a recent large series reported that about 10% of patients underwent this procedure [18]. Similarly, its relevance remains under debate [19]. Nevertheless, we wanted to highlight that 12% of patients in our series who underwent an exploratory laparoscopy were finally found to have a contraindication to resection intraoperatively (with a "short" delay from laparoscopy to exploration of 18 days).…”
Section: Stagingmentioning
confidence: 97%